Performance of One-Stage of Multi-Stage Flash System - Abdolreza, Toudehdehghan; Esraa Ashraf, Sadik Hassan (INTI International University, 2022)
One of the most extensive desalination facilities, the multi-stage flash (MSF) system uses saltwater to create desalinated water, which is then utilized to develop high productivity fresh (sweet) or non-salt water. The operation of MSF plants is depending on using thermal energy to evaporate some vapor (pure water) from the seawater based on the reduction in the operating pressure, which the generated vapor will condense to form the product. This article will outline the design of the brine heater and the one-stage (just the first stage) MSF system. The thermal performance (MSF plant efficiency) of the suggested system (one-stage of MSF), measured by Gain Output Ratio, reaches 0.45 (very low value). Therefore, the MSF plants must be designed with multi-stages to increase its thermal performance. A parametric study has been done to study the effect of tube length and vapor temperature on the number of tubes.